Preparation of ZnO Nanoparticles Under Ultrasonic Irradiation and Photocatalytic Performance of ZnO Nanoparticles Multilayer Films - Soo Park, Hae; Bae Ko, Weon (Asian Journal of Chemistry, 2014)
Zinc oxide nanoparticles were synthesized by the reaction of an aqueous-alcoholic solution containing zinc nitrate hexahydrate and sodium hydroxide under ultrasonic irradiation at room temperature. The crystallinity, morphology and optical property of ZnO nanoparticles were examined by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and UV-visible spectrophotometer. Zinc oxide nanoparticles multilayer films were prepared dipping glass slide, which had been cleaned with a piranha solution, into a ZnO solution by ultrasonic irradiation. The ZnO nanoparticles multilayer films were evaluated as a photocatalyst in the photocatalytic degradation of organic dyes, such as methylene blue, methyl orange and rhodamine B, under ultraviolet light at 254 nm.